Where Are All the Other Fat Folks? Fat Liberation in Food Justice Work - Potvin, Leigh (Canadian Woman Studies/les cahiers de la femme, 2023)
This paper includes first-person narratives about my experiences as a fat (white, cis, queer) academic and teacher involved in community food justice research and advocacy. Theoretically grounded in fat studies and food studies, I explore the tensions amongst these disciplines and suggest that justice-minded food folks should also be focused on fat inclusion, addressing implicit bias in food advocacy spaces, celebrating food and community, and advocating for systemic change that supports fat liberation.